PENGARUH KELELAHAN KERJA TERHADAP KELUHAN MUSCULOSKELETAL DISORDERS (MSDs) PADA PEKERJA WANITA DI PT AMTEK PLASTIC BATAM - Susoko, Yohanes Josua Pranata; Zetli, Sri (LPPM Universitas Putera Batam, 2023)
Employees work standing and chairs without backrests with repetitive leg and hand movements during work with a normal 8-hour period. Production machines and seats are designed without taking into account the anthropometry of workers, anthropometry is needed in the design of tools and work equipment. The purpose of anthropometry in designing tools and equipment is to make harmony between humans and work systems, so that labor can work comfortably. So that workers must adjust themselves at work conditions like this force workers to always be in an unergonomic attitude and work position that lasts a long time. The purpose of this study is to determine the level of work fatigue, determine the risk factors of musculoskeletal disorders (Msds) and determine the effect of Work Fatigue on Complaints of Musculoskeletal Disorders (Msds) in Female Workers. The method used is simple regression analysis, work fatigue is measured using the IFRC (international fatigue research committee of japan association of industrial health) method and complaints of musculoskeletal disorders (Msds) are measured using the Nordic body map (NBM) method. The results showed there is an influence between job fatigue and musculoskeletal disorders (Msds) complaints in female workers at PT Amtek Plastic Batam.